2010
DOI: 10.1124/dmd.110.035691
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Induction of CYP2A5: Permissive Role for CYP2E1

Abstract: ABSTRACT:CYP2A5 metabolizes xenobiotics and activates hepatocarcinogens, and induction occurs in response to hepatic damage and cellular stress. We evaluated whether ethanol can elevate CYP2A5 and whether CYP2E1 plays a role in the ethanol induction of CYP2A5. Wild-type (WT), CYP2E1 knockout (KO), and CYP2E1 knockin (KI) mice were fed ethanol for 3 weeks. Ethanol increased CYP2E1 and CYP2A5 protein and activity in WT mice but not in the KO mice. Induction of CYP2A5 (and CYP2E1) was restored in the KI mice. Eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 37 publications
(61 reference statements)
6
53
0
Order By: Relevance
“…Our findings are consistent with a human study that showed no association between the level of alcohol intake and in vivo CYP2A6 activity in a population of moderate alcohol consumers (Mwenifumbo et al, 2007). It has been proposed that hepatic CYP2A6 may be induced in response to ethanolmediated oxidative stress and/or liver damage (Lu et al, 2011). Treatment with 100 mM ethanol induced CYP2A6 in a human monocytic cell line, and this induction was blocked by pretreatment with the antioxidant vitamin C, suggesting a role for oxidative stress in the regulation of CYP2A6 (Jin et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with a human study that showed no association between the level of alcohol intake and in vivo CYP2A6 activity in a population of moderate alcohol consumers (Mwenifumbo et al, 2007). It has been proposed that hepatic CYP2A6 may be induced in response to ethanolmediated oxidative stress and/or liver damage (Lu et al, 2011). Treatment with 100 mM ethanol induced CYP2A6 in a human monocytic cell line, and this induction was blocked by pretreatment with the antioxidant vitamin C, suggesting a role for oxidative stress in the regulation of CYP2A6 (Jin et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Elevated levels of CYP2A6 and CYP2B6 protein have been reported in livers from alcoholics (Niemelä et al, 2000;Hesse et al, 2004). Chronic ethanol administration induces protein levels of hepatic CYP2A5 (orthologue to human CYP2A6) in mice (Lu et al, 2011) and hepatic CYP2B1/2 (orthologue to human CYP2B6) in rats (Howard et al, 2001), suggesting that ethanol exposure may be responsible for the higher levels of CYP2A6 and CYP2B6 in alcoholics; however, the induction of these hepatic enzymes by ethanol has not yet been demonstrated in primates.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CYP2E1-dependent ROS was needed for CYP2A5 induction through activation of the NRF2 (Lu et al, 2012). Since CYP2A5 can also metabolize many cancer causing agents, such as aflatoxin B1 and nitrosamines, the induction of CYP2A5 in rodents by alcohol (Lu et al, 2011) or HFD and CYP2A6 in alcoholic individuals is likely to contribute to increased oxidative stress and hepatic injury in ALD and NALD.…”
Section: Role and Regulation Of Xanthine Oxidase In Liver Diseasementioning
confidence: 97%
“…In mice, alcohol feeding induces CYP2A5 in a CYP2E1-dependent manner (Lu et al, 2011), possibly through the CYP2E1-ROS-Nrf2 axis (Lu, Zhang, & Cederbaum, 2012). Elevated levels of hepatic CYP2A6 (the human ortholog of the mouse CYP2A5) were also observed in some patients with ALD or cirrhosis than the control, despite the small sample size (Lu et al, 2011). In the mouse model, ethanol-mediated CYP2A5 induction was dependent on the presence of CYP2E1, while ethanol induction of CYP2E1 was not CYP2A5 dependent.…”
Section: Role and Regulation Of Xanthine Oxidase In Liver Diseasementioning
confidence: 97%
See 1 more Smart Citation